Relationship between Ferritin Levels with Calcium Levels in Patients Thalassemia β Major in Hospital in Jember - Fantya Cerebella Aslamy; Rini Riyanti; Cholis Abrori (Journal of Agromedicine and Medical Sciences, 2023)
Thalassemia β major is a hereditary disorder caused by mutations in the β-globin gene, which regulates the formation of one of the components that make up hemoglobin. This disorder results in the production of β-globin chains being reduced or not formed. The prevalence of thalassemia carriers in Indonesia reached 3.8% of the entire population based on data from the Ministry of Health in 2019. Therapy for thalassemia β major patients is lifelong transfusion, which results in iron overload and triggers hypocalcemia and osteoporosis. The aim of this study was to determine the relationship between ferritin levels and calcium levels in thalassemia β major patients. This study uses an observational analytic research type and a cross-sectional research design. This research was conducted at the RSD dr. Soebandi Jember, Jember Clinic Plantation Hospital, and in December 2019-January 2020. The total sample was 13 patients suffering from thalassemia β major aged 1-18 years. The results of the Pearson analysis showed that p=0.858 showed that there was no ignificant correlation between ferritin levels and calcium levels in Thalassemia β major in Jember. Keywords: Thalassemia β major, ferritin levels, calcium levels, hypocalcemia